(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Water surface temperature is an important factor influencing the ecological state of the lake. Remote sensing techniques are an important tool for obtaining lake surface water temperature, which provides periodic information from the entire surface of the lake. The aim of this study is to analyze the spatiotemporal change of Lake Sevan surface water temperature based on remote sensing data and to analyze the relationship between the surface temperature of the lake water and the air temperature of the lake basin. The results confirm the relationship between the water surface temperature of Lake Sevan and the air temperature in the lake basin. Under conditions of reliability p<0.01, the following correlation results were obtained: between average ten-day water surface temperatures and ten-day air temperatures with coefficient r=0.929, between average monthly water surface temperatures and monthly maximum air temperatures with coefficient r=0.918, between the monthly maximum water surface temperature and the monthly maximum air temperature with a coefficient of r=0.961. Analysis of remote sensing data shows both patterns and anomalous behavior of lake surface water temperature.